2014
DOI: 10.1002/mc.22252
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the proapoptotic tumor suppressor gene Cell Adhesion Molecule 1 by chemotherapeutic agents is repressed in therapy resistant acute myeloid leukemia

Abstract: Even though a large proportion of patients with acute myeloid leukemia (AML) achieve a complete remission upon initial therapy, the majority of them eventually relapse with resistant disease. Overexpression of the gene coding for the transcription factor Ecotropic Virus Integration site 1 (EVI1) is associated with rapid disease recurrence and shortened survival. We therefore sought to identify EVI1 target genes that may play a role in chemotherapy resistance using a previously established in vitro model system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Concerning expression analyses, cells were prepared and, where indicated, treated with araC (4 µM for 48 h) as described previously [34,55]. Regarding metabolic activity assays, vitally frozen AML cells were thawed, washed with RPMI 1640 medium (Invitrogen, CA, USA) supplemented with 10% fetal bovine serum (FBS; Invitrogen), 1% Penicillin/Streptomycin/Glutamine (Invitrogen), and 5 µg/mL DNase (Sigma–Aldrich, Missouri, USA), and incubated for 60 min at 37 °C and 5% CO 2 with RPMI 1640 medium containing 10% FBS, 1% Penicillin/Streptomycin/Glutamine, and 50 µg/mL DNase to prevent cell clumping.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning expression analyses, cells were prepared and, where indicated, treated with araC (4 µM for 48 h) as described previously [34,55]. Regarding metabolic activity assays, vitally frozen AML cells were thawed, washed with RPMI 1640 medium (Invitrogen, CA, USA) supplemented with 10% fetal bovine serum (FBS; Invitrogen), 1% Penicillin/Streptomycin/Glutamine (Invitrogen), and 5 µg/mL DNase (Sigma–Aldrich, Missouri, USA), and incubated for 60 min at 37 °C and 5% CO 2 with RPMI 1640 medium containing 10% FBS, 1% Penicillin/Streptomycin/Glutamine, and 50 µg/mL DNase to prevent cell clumping.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 261 DE genes were detected (140 up-and 121 downregulated; p < 0.01; log 2 FC % À0.6 or log 2 FC R 0.6; Table S4), and GSEA analysis showed that the gene-expression profile associated with ectopic expression of Id2 in Tet-off MLL-AF9 (MLL-AF9 ON) leukemias was highly enriched in genes negatively correlated with the LSC signature identified by Somervaille et al (2009) in MLL-rearranged leukemia ( Figure S5F). Id2 overexpression (Table S4) affected many genes involved in hematopoiesis, cytokine signaling, and inflammation/myeloid differentiation, including some previously reported to be associated with pro-(such as Gpr56, Cxxc5, and Prkca) or anti-leukemogenic (such as Tgif1 and Cadm1) effects in AML ( Figure S5G) (Fisser et al, 2015;Kornblau et al, 2006;Kuhnl et al, 2015;Pabst et al, 2016;Willer et al, 2015).…”
Section: Id2 Expression Inhibits Mll-af9-driven Leukemia Development mentioning
confidence: 95%
“…CADM1 expression is frequently lost in numerous types of epithelial neoplasms ( 13 15 ), and CADM1 is considered to be a tumor suppressor in epithelial neoplasms. In contrast, upregulated CADM1 appears to promote ATLL ( 16 ) and AML ( 17 ) progression through enhancement of tumor cell growth, tissue invasion, and adhesion to the vascular endothelium ( 18 ). There is also recent research that high CADM1 expression in SCLCs might promote the malignant features of the cancer ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CADM1 in those cancers is considered to act as a tumor suppressor. In contrast, CADM1 appears to be a tumor promoter in adult T cell leukemia/lymphoma (ATLL) ( 16 ) and acute myelocytic leukemia ( 17 , 18 ), which show high CADM1 expression with enhancement of tumor growth, tissue invasion by the tumor cells, and tumor cell adhesion to the vascular endothelium ( 18 ). Recent research also reported that CADM1 is highly expressed in ~80% of small cell lung cancers (SCLCs) and promotes malignant features of them ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%